Association between number of prostate biopsies and patient‐reported functional outcomes after radical prostatectomy: implications for active surveillance protocols. (20th July 2015) - Anderson, Christopher B.; Tin, Amy L.; Sjoberg, Daniel D.; Mulhall, John P.; Sandhu, Jaspreet; Touijer, Karim; Laudone, Vincent P.; Eastham, James A.; Scardino, Peter T.; Ehdaie, Behfar
Abstract : Objectives: To evaluate whether the number of preoperative prostate biopsies affects functional outcomes after radical prostatectomy (RP). Methods: We identified patients treated with RP at our institution between 2008 and 2011. At 6 and 12 months postoperatively, the patients completed questionnaires assessing erectile and urinary function. Patients with preoperative incontinence or erectile dysfunction or who did not complete the questionnaire were excluded. Primary outcomes were urinary and erectile function at 12 months postoperatively. We used logistic regression to estimate the impact of number of prostate biopsies on functional outcomes after adjusting for demographic and clinical factors. Results: We identified 2 712 patients treated with RP between 2008 and 2011. Most of the patients (80%) had one preoperative prostate biopsy, 16% had two, and 4% had at least three. On adjusted analysis, erectile function at 12 months was not significantly different for patients with two (odds ratio [OR] 1.25; 95% confidence interval [CI] 0.90, 1.75) or three or more (OR 1.52; 95% CI 0.84, 2.78) biopsies, compared with those with one biopsy. Similarly, urinary function at 12 months was not significantly different for patients with two (0.84, 95% CI 0.64, 1.10) or three or more (0.99, 95% CI 0.60, 1.61) biopsies compared with those with one. Conclusions: We did not find evidence that a greater number of preoperative prostate biopsies adversely affected erectile or urinary function at 12 months after RP.